Regulation by Per-Arnt-Sim (PAS) kinase of pancreatic duodenal homeobox-1 nuclear import in pancreatic β-cells. (25th October 2006) - An, R.; da Silva Xavier, G.; Hao, H.-X.; Semplici, F.; Rutter, J.; Rutter, G.A.
Abstract : The transcription factor PDX-1 (p ancreatic d uodenal homeobox -1) is required for normal pancreatic development and for the function of insulin-producing islet β-cells in mammals. We have shown previously that glucose regulates insulin gene expression in part through the activation and translocation of PDX-1 from the nuclear periphery to the nucleoplasm. We have also found that PASK [PAS (Per-Arnt-Sim) kinase], a member of the nutrient-regulated family of protein kinases, is activated in response to glucose challenge in β-cells and is involved in the regulation of expression of PDX-1. Purified PASK efficiently phosphorylated recombinant PDX-1 in vitro on a single site (Thr-152). To determine the impact of phosphorylation at this site, we generated wild-type and mutant (T152A, T152D and T152E) forms of PDX-1 and examined the distribution of each of these in clonal MIN6 β-cells by immunocytochemical analysis. Unexpectedly, only the T152D mutation significantly affected subcellular distribution, increasing the ratio of nuclear/cytosolic labelling at low and high glucose concentrations, suggesting that phosphorylation at Thr-152 inhibits nuclear uptake in response to glucose. Based on these results, experiments to examine the contribution of Thr-152 to the overall phosphorylation of PDX-1 in intact cells will be undertaken.